A System for Notification of Road Accident, Fire and Injury Cases: Smart Emergency Notification System (SENS) - Yıldız, Emre Rifat (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
In this thesis, the system named Smart Emergency Notification System (SENS) is proposed for both the emergency responders and community. SENS detects the single/multiple emergency case(s), i.e. road accident, fire and injury, automatically from the image sent by a smartphone via Internet by the proposed promising approach that uses data mining and machine learning techniques with Cloud Vision API service of Google and afterwards, notifies police, fire brigade and/or ambulance. This system has three modules which are the mobile application SENSdroid, the Web application WebSENS and the software agent NotiSENS that uses the proposed approach. It is possible to say that this system would has positive effect on helping the harmed person, supporting the staff on duty, protecting the person who can be harmed and/or saving the nature. Additionally, this system would has high usability because of its easy-to-use features and high rates of smartphone and Internet users. It is believed that SENS could be an efficient and useful system. Keywords: Emergency Case Detection, Emergency Notification, Machine Learning, Data Mining, Mobile Application, Web Application, Agent, Cloud Vision API, Smart System.

ÖZ: Bu tezde, toplum ve acil durum yanıtlayıcıları tarafından kullanılması amaçlanan Akıllı Acil Durum Bildirim Sistemi adlı bir sistem önerilmiştir. Bu sistem makine öğrenimi ve veri madenciliği tekniklerini Google Inc.’in bir servisi olan Cloud Vision API ile birlikte kullanan bir yaklaşıma dayalı olarak çalışır. Trafik kazası, yangın ve yaralanma acil durumları tekli/çoklu olarak, akıllı telefon aracılığıyla İnternet üzerinden gönderilen resimlerin önerilen yaklaşıma göre işlenmesiyle otomatik olarak tanımlanır ve polis, itfaiye ve/veya ambulans olmak üzere acil durum yanıtlayıcılarından ilgili olan(lar)a bildirilir. Sistemin, SENSdroid adlı bir mobil uygulama, WebSENS adlı bir İnternet uygulaması ve önerilen yaklaşıma dayalı olarak çalışan NotiSENS adlı bir yazılım ajanı olmak üzere üç modülü bulunmaktadır. Bu sistemin zarar gören kişilere yardım etme, görevli personeli destekleme, zarar görebilecek kişiyi koruma ve/veya doğayı koruma konularında olumlu etkilerinin olacağını söylemek mümkündür. Buna ek olarak, sistemin kolay kullanım özellikleri ve yüksek oranda akıllı telefon ve İnternet kullanıcısı olması nedeniyle geniş bir kullanıcı kitlesine sahip olacağı düşünülmektedir. Bu sebeple, sistemin etkili ve faydalı bir çözüm olabileceğine inanılmaktadır. Anahtar Kelimeler: Acil Durum Tanımlama, Acil Durum Bildirimi, Makine Öğrenimi, Veri Madenciliği, Mobil Uygulama, Web Uygulaması, Yazılım Ajanı, Cloud Vision API, Akıllı Sistem.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2015. Supervisor: Assist. Prof. Dr. Yıltan Bitirim.
Keywords: Computer Engineering; Computational intelligence--Smart Emergency Notification Systems; Machine learning--Smart Computer Systems; Emergency Case Detection; Emergency Notification; Machine Learning; Data Mining; Mobile Application; Web Application; Agent; Cloud Vision API; Smart System